Unhealthy Alcohol Use is Associated with Monocyte Activation Prior to Starting Antiretroviral Therapy - Carrico, Adam W.; Hunt, Peter W.; Emenyonu, Nneka I.; Muyindike, Winnie; Ngabirano, Christine; Cheng, Debbie M.; Winter, Michael R.; Samet, Jeffrey H.; Hahn, Judith A. (Clinical and Experimental Research, 2015)
Background: Alcohol use may accelerate HIV disease progression, but the plausible biological mechanisms have not been clearly elucidated. Methods: HIV-positive persons who were not on antiretroviral therapy (ART) completed the baseline assessment for a longitudinal study examining the association of alcohol use with HIV disease markers. Oversampling drinkers, baseline samples were tested for markers of monocyte activation (soluble CD14 [sCD14]), inﬂammation (interleukin-6 [IL-6]-6), and coagulation (D-dimer). We deﬁned “unhealthy alcohol use” as testing positive using the Alcohol Use Disorders Identiﬁcation Test— Consumption (≥3 for women and≥4 for men) in the past 3 months or testing positiveusing a biomarker of heavy drinking, phosphatidylethanol (≥50 ng/ml). Multiple linear regression was used to examine the associations of unhealthy alcohol use with sCD14, log10 IL-6, and D-dimer. Results: Compared to those who were abstinent from alcohol, unhealthy drinkers had signiﬁcantly higher sCD14 levels (mean = 1,676 vs. 1,387 ng/ml; mean diﬀerence [95% conﬁdence interval (CI)] = 289 [83, 495], p < 0.01). In analyses adjusted for demographic factors, current cigarette smoking, and HIV disease markers, unhealthy drinkers continued to display signiﬁcantly higher sCD14 levels compared to those who were abstinent from alcohol (adjusted mean = 1,670 vs. 1,406 ng/ml; adjusted mean diﬀerence [95% CI] = 264 [47, 480], p = 0.02). Unhealthy alcohol use was not signiﬁcantly associated with IL-6 or D-dimer levels. Conclusions: Unhealthy alcohol use was independently associated with a marker of monocyte activation (i.e., higher sCD14) that predicts mortality in treated HIV infection. Longitudinal research should examine whether unhealthy alcohol use predicts changes in sCD14 prior to and following ART initiation.
Keywords: Alcohol; HIV/AIDS; Immune Activation; Microbial Translocation